2010
DOI: 10.1007/s00249-010-0648-1
|View full text |Cite
|
Sign up to set email alerts
|

Fast uncoiling kinetics of F1C pili expressed by uropathogenic Escherichia coli are revealed on a single pilus level using force-measuring optical tweezers

Abstract: Uropathogenic Escherichia coli (UPEC) express various kinds of organelles, so-called pili or fimbriae, that mediate adhesion to host tissue in the urinary tract through specific receptor-adhesin interactions. The biomechanical properties of these pili have been considered important for the ability of bacteria to withstand shear forces from rinsing urine flows. Force-measuring optical tweezers have been used to characterize individual organelles of F1C type expressed by UPEC bacteria with respect to such proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 49 publications
6
33
1
Order By: Relevance
“…21,22,43 The dependence of CFA/I (colonization factor antigen I) pili rupture force on pulling rate was observed for pulling rate larger than a critical value (1.4 µm/s) referred to as the corner velocity. 21 Our results are consistent with pulling rate dependentrupture force and elongation as reported for CFA/P/I pili 19,22,44 , and they additionally evidence a strong influence of solution pH on the extent of fimbrial unwinding, as schematically illustrated in Figure S5 and Figure S6.…”
Section: The Retraction Force Curves Depicted In Figures 2a 2b Were supporting
confidence: 79%
See 1 more Smart Citation
“…21,22,43 The dependence of CFA/I (colonization factor antigen I) pili rupture force on pulling rate was observed for pulling rate larger than a critical value (1.4 µm/s) referred to as the corner velocity. 21 Our results are consistent with pulling rate dependentrupture force and elongation as reported for CFA/P/I pili 19,22,44 , and they additionally evidence a strong influence of solution pH on the extent of fimbrial unwinding, as schematically illustrated in Figure S5 and Figure S6.…”
Section: The Retraction Force Curves Depicted In Figures 2a 2b Were supporting
confidence: 79%
“…It was reported that both pili are highly flexible and they may be viewed as dynamic structures with spring-like properties. 5,[16][17][18] Indeed, when bacteria were subjected to hydrodynamic constrains, these structures maintain bacterial attachment to host cells or surfaces by reducing the impact of flushes and associated mechanical stress 5,19 following an unwinding of the pointed out that the length of P-pili and type 1 fimbriae could increase by a factor 5 following such unwinding process under high shear stress conditions. [20][21][22] The forced unraveling of type 1 fimbriae is reversible, with helical rewinding taking place for shear forces of magnitude ~ 60 pN.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the force response of multiple fimbriae was additive, as seen for other helix-like fimbriae (39). Fig.…”
Section: Cs2 Fimbrial Response To Tensile Forcementioning
confidence: 74%
“…ETEC fimbriae such as CS2, CFA/I, and CS20 require <15 pN unwinding force, despite differences in their assembly mechanism (see Table S1 and our previous work (24,26)); UPEC and meningitis-associated strains of E. coli express fimbriae requiring 21-30 pN of unwinding force (33,39,42); however, Type 3 fimbriae expressed by K. pneumonia in the respiratory tract require 66 pN of unwinding force (43). One should also note that the T4 fimbriae expressed by Streptococcus pneumonia, which also colonize the respiratory tract, are significantly stiffer than UPEC-and ETEC-expressed fimbriae (45).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation